THE INFLUENCE OF INTERPERSONAL COMMUNICATION AND SERVICE QUALITY ON MEDAN STATE UNIVERSITY LIBRARY SATISFACTION - Amin, Afriadi (Universitas Dharmawangsa Medan, 2025)
The aim of this research is to analyze the influence of interpersonal communication and service quality on user satisfaction at Medan State University. This research uses effective understanding in interpersonal communication and finds out what influence users have in visiting the library at Medan State University. This data collection technique is through observation and documentation. This data analysis technique uses thematic analysis. In providing services, librarians must foster positive, transparent and interpersonal relationships by providing services that make librarians very happy when visiting the library. Communication is a very important factor in working between humans and other people in the work environment, for example between employees in the same position or employees in different positions. The aim of this research is to obtain information or feedback and improve user-friendly services, which is a form of collaboration between users and librarians to understand the aims and objectives. It is concluded that librarians can be defined as library employees who are intended to provide services to the public or library users, based on knowledge obtained through training, literature and library information.